A new species and a new synonymy of the plant bug genus Fulvius from Japan (Hemiptera: Heteroptera: Miridae: Cylapinae) - Yasunaga, Tomohide; Wolski, Andrzej (Zootaxa, 2017)
Fulvius Stål (Cylapinae: Fulviini) is a large plant bug genus, with more than 80 described species distributed throughout the world (Schuh, 1995; 2002–2014). In Japan, five species listed below have been recorded mostly from the subtropical Ryukyu arc (Yasunaga, 2000, 2001; Yasunaga & Miyamoto, 2006; Yasunaga et al., 2012). Our recent closer examinations of these Japanese species suggest that (1) what was previously identified as Fulvius dimidiatus Poppius represents an undescribed species, and (2) F. nakatai Yasunaga & Miyamoto described from Okinawa Island is evidently conspecific with F. subnitens Poppius that was described from New Guinea but is now known from pantropical zones as well as Taiwan, Europe and United States (Gorczyca, 2006; Henry et al., 2011). The present paper provides a revised checklist for the Japanese species of Fulvius, with updated distributional records. A new species, F. nozawai, is diagnosed and described, its habitat and biology are also documented, and Fulvius nakatai is proposed as a junior synonym of the pantropical F. subnitens.